The hidden impact of myopia severity on interocular suppression in myopia: a cross-sectional study - Luo, Yan; Yang, Xiyang; Lin, Enwei; Kong, Min; Luo, Wuqiang; Chen, Qi; Zeng, Jin; Yan, Li; Li, Lili; Xiao, Xin (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the association between spherical equivalent (SE) and interocular suppression in myopic adults, addressing the knowledge gap in functional visual impairments beyond structural changes.MethodsThis hospital-based cross-sectional study included 988 myopic patients (aged 18.0–48.7 years, SE ≥ 0.50D). Grating stereopsis (GS), fine stereopsis at 1.5 m (FS1.5), fine stereopsis at 0.8 m (FS0.8), division, fusion, and interocular suppression were examined via computer-based tasks. Multivariate logistic regression analysis and restricted cubic splines (RCSs) were used to analyze the dose–response relationships between SE and the prevalence of suppression disorders (permanent suppression or binocular rivalry suppression). Sensitivity analysis and subgroup analysis were used.ResultsThe prevalence of suppression disorders was 30.6%. Multivariate logistic regression analysis revealed a dose–response relationship between SE and the prevalence of suppression disorder (odds ratio [OR]: 1.08, 95% CI: 1.00–1.17, p = 0.044) after adjusting for age, sex, anisometropia, cylindrical anisometropia, division, fusion, best corrected visual acuity (BCVA), FS0.8, FS1.5, and GS. Restricted cubic splines analysis revealed that the odds ratio of suppression disorder increased approximately linearly with the increase in spherical equivalent (P for non-linearity = 0.7633 > 0.05). Subgroup analyses showed that this association persisted in those aged <25 years (OR: 1.15; 95% CI: 1.04 ~ 1.27, p = 0.006), those with normal GS (OR: 1.17, 95% CI, 1.03–1.34, p = 0.020), and those with normal FS0.8 (1.09, 95% CI: 1.01–1.18, p = 0.026). In a sensitivity analysis that categorized myopia into three groups, a statistically significant positive association between high myopia (OR: 1.87, 95% CI: 1.10–3.29, p = 0.025), moderate myopia (OR: 1.75, 95% CI: 1.04–3.03, p = 0.039), and suppression disorder was found after adjustment for covariates.ConclusionMyopia severity independently correlates with suppression disorders, suggesting the need for functional vision screening and personalized myopia correction strategies in high-risk populations.